1990
DOI: 10.1164/ajrccm/142.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Antituberculous Drug Resistance in Central Haiti

Abstract: To determine the prevalence of antituberculous drug resistance in Haiti, we conducted a 1-yr survey in a central district. From a bacillary positive (smear and/or culture positive) case rate of 80/100,000, there were 282 patients from whom Mycobacterium tuberculosis was cultured. Each isolate was packaged and delivered to Canada where speciation and drug susceptibility testing were performed. Reported resistances are those using the proportions method (Laboratory Center for Disease Control, Ottawa, Canada). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 1 publication
0
14
1
Order By: Relevance
“…The age of the patients and previous history of hepatic cirrhosis were also independent risk factors in the presence of resistance to antituberculosis drugs. SCALCINI et al [30], in Haiti, described an increase in resistance with age, although other writers have not observed this relationship [2,4,16]. In our study, those patients who were 45 or more years of age presented a risk almost four times higher than those of less than 45 yrs, even adjusting for other potential risk factors.…”
Section: Discussioncontrasting
confidence: 64%
“…The age of the patients and previous history of hepatic cirrhosis were also independent risk factors in the presence of resistance to antituberculosis drugs. SCALCINI et al [30], in Haiti, described an increase in resistance with age, although other writers have not observed this relationship [2,4,16]. In our study, those patients who were 45 or more years of age presented a risk almost four times higher than those of less than 45 yrs, even adjusting for other potential risk factors.…”
Section: Discussioncontrasting
confidence: 64%
“…(7,8) Studies from the neighboring Dominican Republic, which shares the island of Hispanola with Haiti, also have shown high MDR-TB rate of 10.2% in all cases and 6.6% of new TB cases. (11) Given the large amount of immigration between countries throughout the western hemisphere, the results of these studies are of particular concern for the spread of previously localized disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a 1990 study, the rate of isoniazid resistance was 19% but multidrug resistant tuberculosis (MDR-TB), defined as resistance to both isoniazid and rifampin, was not found in any patient with new tuberculosis. (7) In a 1991 study of recent migrants from Haiti to Cuba, single drug resistance to isoniazid was found in 22% of TB patients but MDR-TB was not found. (8) However, a study in 2002 of patients presenting to an HIV/AIDS center in Port au Prince with new onset tuberculosis found a rate of primary multidrug-resistant tuberculosis of 6%.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory data: Isolates were processed with the radiometric system (BACTEC 460, Becton-Dickinson Diagnostic Instrument Systems, Maryland). Details of this method have been described previously (6). In each provincial mycobacterialogy laboratory the BACTEC system had been validated against the proportion method used by the Laboratory Centre for Disease Control, Ottawa, Ontario.…”
Section: Methodsmentioning
confidence: 99%